2014
DOI: 10.1007/s10071-014-0752-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictability and heritability of individual differences in fear learning

Abstract: Our objective was to characterize individual differences in fear conditioning and extinction in an outbred rat strain, to test behavioral predictors of these individual differences, and to assess their heritability. We fear-conditioned 100 Long-Evans rats, attempted to extinguish fear the next day, and tested extinction recall on the third day. The distribution of freezing scores after fear conditioning was skewed, with most rats showing substantial freezing; after fear extinction, the distribution was bimodal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
52
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 43 publications
12
52
1
Order By: Relevance
“…As seen by others in rat strains [12, 13, 17], Long Evans rats showed significant individual differences in the extinction of cue-conditioned freezing. For analysis purposes, animals were divided into high and low freezing groups based on a median split of the average percent freezing observed during the last 10 minutes of the cue (within trial extinction) session.…”
Section: 0 Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…As seen by others in rat strains [12, 13, 17], Long Evans rats showed significant individual differences in the extinction of cue-conditioned freezing. For analysis purposes, animals were divided into high and low freezing groups based on a median split of the average percent freezing observed during the last 10 minutes of the cue (within trial extinction) session.…”
Section: 0 Resultssupporting
confidence: 54%
“…Analysis of the behavioral data in the 23 animals during the extinction trial suggested that the data were not normally distributed (Shapiro-Wilk normality test, P<0.004). A frequency distribution analyzing the average percent freezing during the last 10 tone presentations of the first extinction trial suggested distinct groups of subjects within the population, similar to differences in extinction learning/recall seen by other groups [12, 13]. Therefore, for analysis purposes, animals were divided into high and low freezers based on a median split of the average percent freezing duration during the last 10 minutes of the cue trial (within trial extinction) on day 3 of the protocol.…”
Section: 0 Methodsmentioning
confidence: 80%
“…11 for a detailed description of selection criteria and breeding procedures). Briefly, for four generations, Long-Evans rats were fear conditioned to a pure tone (20 s, 5 kHz, 80 dB) co-terminating with a footshock (0.7 mA for 0.5 s).…”
Section: Methodsmentioning
confidence: 99%
“…In this direction, it has been shown that individual differences are important predictors for the reactivity to stressful stimulation [7][8][9]. The reasons and specific individual traits that can contribute to variations on the expression of defensive behaviors are still unclear, although being under intense investigation [10,11].…”
Section: Introductionmentioning
confidence: 97%